Ventriculoperitoneal Shunt Infection and Treatment in Children - (:unkn) unknown (CUKUROVA UNIV, FAC MEDICINE, 2015)
Purpose: The most important complication of ventriculoperitoneal shunt (VPS) surgery is central nervous system infections developing in the postoperative period. The incidence of VPS infection in cases with VPS inserted is known to be between 6.5-23.5%. The aim of this study is to evaluate the treatment and complications relating to VPS surgery infections in pediatric patients with hydrocephalus. Material and Methods: Patients between January 2011 and January 2013 with VPS inserted for hydrocephalus and complications relating to infections after surgical intervention were included in the study. The patient files were retrospectively investigated and analyzed. Patients were evaluated based on demographic characteristics, etiology of hydrocephalus, date of shunt insertion, operation notes from the VPS insertion operation, microbiological and biochemical test results on CSF samples after diagnosis of VPS infection, surgical intervention for treatment, antibiotics administered and duration of antibiotic use. Results: Thirty-five patients monitored for VPS infection diagnosis between the ages of 3 days and 16 years were evaluated. In the 35 patients monitored for VPS infection diagnosis 19 had growth in cerebrospinal fluid (CSF) while 17 patients had no growth in CSF but inflammatory findings were present. The most frequently isolated effective pathogens were coagulase-negative staphylococci (78%). Other microorganisms isolated in the CSF of patients were Staphylococcus aureus, Enterococcus feacalis, Enterococcus gallinarium, Pseudomonas stutzeri, Candida albicans, Streptococcus mitis and ESBL (-) Klebsiella pneumonia. While one patient died during treatment, 34 patients were successfully discharged. Conclusion: We believe that early administration of antibiotic treatment and removal of the infected shunt are of vital importance.
Keywords: Ventriculoperitoneal Shunt; Infection; Child; Hydrocephalus; CEREBROSPINAL-FLUID SHUNT; PERIOPERATIVE ANTIBIOTIC-PROPHYLAXIS; C-REACTIVE PROTEIN; TERM-FOLLOW-UP; RISK-FACTORS; BACTERIAL-MENINGITIS; MANAGEMENT; HYDROCEPHALUS; EXPERIENCE; SURGERY